Cost-Effectiveness of Reducing Glycaemic Episodes Through Community Pharmacy Management of Patients with Type 2 Diabetes Mellitus - Hendrie, Delia; Miller, T.; Woodman, R.; Hoti, Kreshnik; Hughes, Jeffrey David (Springer, 2014)
Accessibility, availability and frequent public contact place community pharmacists in an ideal position to provide medically necessary, intensive health education and preventive health services to diabetes patients, thus reducing physician burden. We assessed the cost-effectiveness of reducing glycaemic episodes in patients with type 2 diabetes mellitus through a pharmacist-led Diabetes Management Education Program (DMEP) compared to standard care. We recruited eight metropolitan community pharmacies in Perth, Western Australia for the study. We paired them based on geographical location and the socioeconomic status of the population served, and then randomly selected one pharmacy in each pair to be in the intervention group, with the other assigned to the control group. We conducted an incremental cost-effectiveness analysis to compare the costs and effectiveness of DMEP with standard pharmacy care. Cost per patient of implementing DMEP was AU$394 (US$356) for the 6-month intervention period. Significantly greater reductions in number of hyperglycaemic and hypoglycaemic episodes occurred in the intervention relative to the control group [OR 0.34 (95 % CI 0.22, 0.52), p = 0.001; OR 0.54 (95 % CI 0.34, 0.86), p = 0.009], respectively, with a net reduction of 1.86 days with glycaemic episodes per patient per month. The cost-effectiveness of DMEP relative to standard pharmacy care was AU$43 (US$39) per day of glycaemic symptoms avoided. Patients with type 2 diabetes in three surveys were willing to pay an average of 1.9 times that amount to avoid a hypoglycaemic day. We conclude that DMEP decreased days with glycaemic symptoms at a reasonable cost. If a larger-scale replication study confirms these findings, widespread adoption of this approach would improve diabetes health without burdening general practitioners.